Strengthening Children's Mental Health Literacy to Prevent a Spike in Depression in the Digital Generation - Mudafiatun Isriyah; Weni Kurnia Rahmawati; Risa Shoffia; Wahid Suharmawan; J. Agung Indratmoko (CV. Laskar Karya, 2026)
The rapid development of digital technology has influenced children’s lifestyles and social interactions, increasing the risk of psychological problems such as anxiety and depression. This study aims to improve mental health literacy among elementary and junior high school students in Jember through community-based educational and psychoeducational interventions. The program included mental health education, interactive discussions, and emotional awareness activities. Data were collected through questionnaires, observations, and documentation to assess students’ understanding before and after the intervention. The results show a significant improvement in students’ knowledge and awareness of mental health, particularly in emotional recognition, coping strategies, and help-seeking behavior. The interactive approach also encouraged students to express their feelings more openly. These findings suggest that strengthening mental health literacy is an effective preventive strategy to reduce psychological risks among the digital generation. Integrating mental health education into school and community programs, supported by collaboration among schools, parents, and communities, is essential for promoting children’s psychological well-being.